enerapan Problem Based Learning Untuk Meningkatkan Hasil Belajar Muatan IPAS Materi Sistem Pernapasan Manusia Kelas V SD - Faliqulhusna, Daifa; Artharina, Filia Prima; Rahayu, Lilik Puji (JURNAL SINEKTIK, 2025)
The research started from the researcher's observation in class V of SD Supriyadi 02; it was found that some students were distracted while learning, and their learning outcomes were still low, only reaching 42% of the KKM 75. The research was conducted during the first semester of the 2023–2024 academic year, mainly in October and November 2023, in class V of SD Supriyadi 02 in Semarang. The research subjects consisted of 28 students, with 13 boys and 15 girls who were grade V learners. The method used was classroom action research. The purpose of this study is to improve the achievement of learning outcomes in nature subjects on material related to human respiratory organs in class V SD Supriyadi 02 by applying a problem-based learning model. The results showed that the application of the problem-based learning model succeeded in improving the learning outcomes of IPAS in grade V students of SD Supriyadi 02 in the 2023–2024 academic year. Before the PTK was carried out, only 42% of students reached the lower category. However, after the action in cycle 1, there was an increase to 65% in the sufficient category. Furthermore, in cycle 2, there was a further increase to 82% in the good category.